1131 Cardiovascular and Hormonal Responses to Hypoxic Stress in the Preterm Piglet. (October 2012) - Eiby, YA; Staunton, MP; Wright, LL; Lumbers, ER; Colditz, PB; Lingwood, BE
Abstract : Background and Aims: Immature control of the cardiovascular system may be a contributing factor to poor cardiovascular function and associated increases in mortality and morbidity in preterm infants. This study aimed to assess cardiovascular and hormonal responses to a mild hypoxic stress in newborn piglets. Methods: Piglets were delivered by C-section at 97 and 113 days of gestation (term≈115d). An additional preterm group was exposed to maternal glucocorticoid treatment. Changes in mean arterial blood pressure (MAP), skin blood flow and plasma concentrations of adrenalin, noradrenalin, angiotensin II and cortisol were measured in response to acute hypoxia (4% O2 for 20min). Results: Preterm piglets were less likely to exhibit a mature cardiovascular compensatory response to hypoxia (increased MAP and reduced skin blood flow) than term piglets. Plasma adrenalin and noradrenalin concentrations at the end of hypoxia were increased in all groups and were 2–3 fold higher in preterm pigs than in term pigs (P<0.05). Plasma cortisol levels were increased at the end of hypoxia in term piglets (P<0.05) but not in preterm or glucocorticoid exposed preterm piglets. Angiotensin II levels were reduced in glucocorticoid exposed preterm piglets compared to untreated preterm piglets (P<0.05). Conclusions: The reduced cardiovascular compensatory response to hypoxia in preterm pigs is not the result of reduced plasma levels of catecholamines during hypoxia. Low levels of angiotensin II in glucocorticoid exposed preterm piglets may contribute to poor control of skin blood flow during hypoxia.